Potential Radiological Dose of 210Po to Several Marine Organisms in Coastal Area of Coal-Fired Power Plant Tanjung Awar – Awar, Tuban - Chairun Annisa Aryanti; Heny Suseno; Muslim Muslim; Wahyu Retno Prihatiningsih; Siti Nurul Aini (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
NORM (Naturally Occurring Radioactive Material) is a radionuclide element that naturally already exists in the earth. Its concentration can be increased by industrial activities, such as coal-fired power plant (CFPP). Coal-fired power plant activities produce fly ash and bottom ash which will be carried away by the wind and then can enter the CFPP environment, one of which is marine waters and can affect the existence of marine biota. The determination of the radiation dose rate is essential in assessing the risk of radionuclide exposure to the marine environment. This study aims to determine and evaluate the total dose rate of 210Po to marine biota taken from the Karangsari fish market with catchment areas around the waters of CFPP Tanjung Awar – Awar, Tuban, East Java. This research was conducted in April 2021 in the waters of CFPP Tanjung Awar – Awar.  210Po measurement activity was carried out using alpha ray spectrometry at the Marine Radioecology Laboratory of PTKMR-BATAN, then the radiation dose rate was calculated using the ERICA Tool software. The value of the total radiation dose of 210Po on marine biota ranges from 2.70E-1 µGy.hr-1 to 39.70E+0 µGy.hr-1. The radiation dose of 210Po on marine biota measured in the waters of CFPP, has a lower value range than the research result carried out in other countries. Based on the Erica Tools software analysis, the total radiation dose measured on marine organisms in the waters of CFPP Tanjung Awar – Awar, does not give a negatively impact to the marine ecosystems and the sustainability of marine organisms in the study area.